Applications of micro size anorganic membrane of clay, zeolite and active carbon as filters for peat water purification. (February 2020) - Saifuddin, S; Lisa, A; Amalia, Z; Faridah, F; Elfiana, E
Abstract: Ceramic membrane is one of technology membrane which used as a filtration. Filtration process is the easy way to solve the problem for water purification. Ceramic membrane was used as filtration for peat water. Peat water is the surface water of peat soils that contain high organic matter as well as high enough iron, acidic taste with a pH of 3-5 and a low level of hardness. Therefore, one of the managements of peat water is by using ceramic membrane. The goal of this study is making ceramic membrane from clay, zeolite and activated carbon as a filter for peat water. The research was conducted by using ceramic membrane with composition ratio of 80:10:10; 70:20:10; 60:30:10; 50:40:10, respectively, with the temperature of combustion varied from 600, 700 and 800 Degree Celsius, respectively. The ceramic membrane applied as a filtration for peat water. The permeats from filtration process using ceramic membrane had been analyzed parameter which indicate the good quality of peat water. This study obtained the highest Fe2+ removal efficiency in peat water by 100 percent, the highest Mn2+ removal efficiency of 99.94 percent, followed by a TDS removal efficiency of 82.58 percent and turbidity 95.65 percent.